ANALISIS KETERKAITAN MATA KULIAH KURIKULUM TEKNIK INDUSTRI UNPAR - Yogi Yusuf Wibisono; Marihot Nainggolan (Universitas Katolik Parahyangan, 2008)
There are many factors influence the quality of education, one of them is a curriculum. The curriculum contains a set of the plan and the arrangement of the subject content and the way to deliver and to assess it. The learning process in higher education refers to its curriculum. The curriculum can determine the expected graduate competency achievement. The competency includes the theoretical based competency, the practical based competency, and the general competency. In the curriculum development, the relation between the subjects has to be devised. This relation has a meaning that one subject is a prerequisite subject of another subject. The prerequisite subject is required to increase the learning effectiveness, but if there are too many and irrelevant prerequisite subjects for one subject it makes the students be inflexible in planning their study. This research uses the structural equation modeling technique to analyze the relation between the subjects. The result of this research shows that the relation between ETEK → AKB, P3 → SPROD, GTEK → P2P, PSIS → SSIS is not significant, the relation between MTEK → PMES, APK2 → P2P is at the low level, and the rest have the strong relationships.Keywords: a curriculum, a prerequisite subject, structural equation modeling.